How Online Extensive Reading and Listening Program Enhances Students’ Reading and Listening Comprehension: An Experimental Study - Asrimawati, Inayati Fitriyah; Elyani, Eka Puteri; Rosalina, Elsa (Journal of Languages and Language Teaching, 2024)
Encouraging students to repeatedly read and listen to resources can be challenging for language teachers. Although students understand that reading and listening are essential for language acquisition, few spend their free time engaging in these activitiesStudents often remain passive and hesitant to read or listen to English texts on their own due to a lack of understanding of the additional benefits, insufficient guidance on choosing appropriate texts for their proficiency level, and ingrained habits. Therefore, this study aimed to explore the impact of the Online Extensive Reading and Listening (OERL) program on students' reading and listening comprehension. Additionally, it sought to assess the variations in students' performance following exposure to the OERL intervention. This quasi-experimental research utilized a pretest-posttest design, involving sixty eleventh-grade students from a senior high school in Banjarbaru, selected through purposive sampling. Data collection involved administering reading and listening comprehension tests, and MANCOVA test was employed for data analysis. Results indicated a significant positive impact of the OERL program on enhancing students' reading and listening comprehension. Furthermore, noteworthy differences were observed in the reading and listening achievements of students exposed to the OERL program compared to those receiving intensive reading and listening with teacher-selected texts, with a significance level of 0.000. In essence, the OERL program proved valuable in improving students' reading and listening comprehension.Â